PELAKSANAAN PEMBINAAN DAN PENGAWASAN TERHADAP PEJABAT PEMBUAT AKTA TANAH DALAM PENDAFTARAN HAK ATAS TANAH DI KOTA PAYAKUMBUH - Wira, Eka Marwahyuni (UNES Law Review, 2020)
Land Deed Making Officials (hereinafter referred to as PPAT) are general officials who assist the National Land Agency to carry out some of the land registration activities. Article 1 number 1 Government Regulation No. 37 of 1998 concerning Regulations of Position of the Acting Officer for Land Deed states that the PPAT is authorized to make authentic deeds concerning certain legal actions regarding land rights or Ownership Rights in Flats. In carrying out his position PPAT is required to be thorough, careful, orderly and understand the regulations relating to land. In practice, PPAT in carrying out its duties and authorities often makes mistakes both administratively and legally. The results of research and analysis show that the implementation of guidance and supervision of the PPAT in the registration of land rights in Payakumbuh City, carried out by the National Land Agency through the socialization of regulations relating to the PPAT-n, making the deed, making monthly reports, checking the list of books deed, examination of the results of the binding of the deed and examination of evidence of sending the deed The obstacles in the guidance and supervision of PPAT in Payakumbuh City are that there are no operational standards to carry out guidance and supervision of PPAT, lack of Human Resources (HR) / employees, both in terms of quality and quantity of employees, and the unavailability of the budget for the implementation of coaching and supervision of PPAT in the DIPA (List of Budget Implementers) of the Payakumbuh City Land Office.